The hound of the Baskervilles - Doyle, Arthur Conan, Sir, 1859-1930. (New York, N.Y. : Dover, 1994)
Sherlock Holmes is asked to investigate the tale of a hound that haunts the lonely moors around the Baskervilles' ancestral home.
Originally published: London : George Newnes, Ltd., 1902.
Adult
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Supernatural -- Fiction; Holmes, Sherlock (Fictional character) -- Fiction; Mystery fiction; Private investigators -- Fiction; Supernatural -- Fiction; Devon (England) -- Fiction; Devon (England) -- Fiction; Detective and mystery stories